1979
DOI: 10.1007/bf02533420
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of sterologenesis in brain and liver of fetal and suckling rats from dams fed di‐2‐ethylhexyl phthalate plasticizer

Abstract: The effect of di-2-ethylhexyl phthalate (DEHP) on lipid metabolism was studied in liver and brain from fetal rats taken 3 days before parturition from dams receiving dietary DEHP during gestation. In fetuses from rats receiving 0.5% or 1.0% DEHP in a stock diet, the incorporation of 14C-acetate and labeled mevalonate (3H or 14C) into the C27 sterols, C30 sterols, and squalene fractions of brain tissue incubated in vitro was significantly reduced between the confidence limits P <0.05 to P <0.001. When liver fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Plasma lipid-related markers such as total cholesterol (TCH), high density lipoprotein cholesterol (HDL-C) triglyceride (TG) of all treatment groups on the DEHP diet were significantly lower than Control. DEHP has been found to inhibit lipid and sterol synthesis in rats [24,25], but there was no significant improvement by D-allose and D-allulose administration. The relationship between sterol synthesis and oxidative stress is unclear.…”
Section: Second Experimentsmentioning
confidence: 95%
“…Plasma lipid-related markers such as total cholesterol (TCH), high density lipoprotein cholesterol (HDL-C) triglyceride (TG) of all treatment groups on the DEHP diet were significantly lower than Control. DEHP has been found to inhibit lipid and sterol synthesis in rats [24,25], but there was no significant improvement by D-allose and D-allulose administration. The relationship between sterol synthesis and oxidative stress is unclear.…”
Section: Second Experimentsmentioning
confidence: 95%
“…In neonatal rats previously injected with MEHP, very little PAE was detected in their livers (19). Bell et al (49) suggested that DEHP can cross the placental barrier, as evidenced by inhibition of sterologenesis in the brain and in the liver of fetal and suckling rats from dams previously fed with this phthalate. Subsequent reports (50) indicated that fetuses taken by caesarean section from pregnant rats fed DEHP (beginning 5 to 10 days after conception) exhibited an impairment of sterologenesis in brain and liver.…”
Section: Neonatalmentioning
confidence: 99%
“…Altered lipid composition in the brain has also been reported following exposure to DEHP [ 24 , 25 ]. Lipids are biological molecules essential for normal neurodevelopment and are involved in a wide variety of cellular processes, including cellular signalling, protein and receptor trafficking, neurogenesis, and myelination [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slight changes in the abundance of certain lipid species in the brain may drastically alter normal neurodevelopment via membrane stability, cell signalling, and cell survival. A reduction in squalene, C 27 and C 30 sterols, free cholesterol esters, and sphingomyelin (SM) were detected in fetal rat brains following in utero exposure to DEHP [ 24 , 25 ]. DEHP treatment also decreased the concentration of mono- and polyunsaturated fatty acids in fetal rat brains, and reduced the concentration of docosahexaenoic acid (DHA) in cholesterol esters, diacylglycerols, phosphatidylserines, lysophosphatidylcholines (LPC), and SM [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation